Preventive effects on seroma formation with use of the harmonic focus shears after breast reconstruction with the latissimus dorsi flap. Issue 6 (1st November 2016) - Sowa, Yoshihiro; Numajiri, Toshiaki; Kawarazaki, Ayako; Sakaguchi, Kouichi; Taguchi, Tetsuya; Nishino, Kenichi
Abstract: Background: Postoperative seroma is the most common complication of latissimus dorsi (LD) flap surgery for breast reconstruction. The use of EC for elevation of the flap might cause additional risk for seroma formation by injuring surrounding lymph vessels due to heat dispersion. There is a possibility that seroma formation can be prevented by using alternative devices such as harmonic focus (HF) shears that can dissect the tissue simultaneously with sealing the lymph vessels. Methods: Forty-eight patients who underwent breast reconstruction with LD flaps since August 2011 up to April 2015 were enrolled. They were retrospectively split into two groups: 24 in group HF, 24 in group EC (conventional electrocautery). The primary outcome measures were rate of seroma formation and total volume of drain discharge and indwelling period of drainage at the anterior chest and donor site. Secondary outcome measures were length of hospital stay and duration of surgery. Results: The incidence of seroma was 45.8% in the EC group and 20.8% in the HF group. The total volumes of the drain discharge and indwelling period of drainage in the back (donor site) were significantly decreased in the HF group. The length of the hospital stay and surgical time was significantly shorter for the HF group. Conclusions: The use of HF shears on the LD flap donor site is helpful for reducing seroma formation, the length of the drainage period, the surgical time, and the length of the hospital stay.